Peran Marketing Communication dalam Membangun Brand Awareness di The Highland Park Resort Hotel Bogor - Hervina Afrianti Rahayu; Ika Sartika (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Competition in the hospitality industry demands that every brand build strong brand awareness, especially for hotels that provide tourist destinations such as The Highland Park Resort Hotel Bogor. This study aims to analyze the role of marketing communication in building brand awareness through the implementation of integrated marketing communications. The method used is descriptive qualitative through in-depth interviews with the marketing communications team, as well as observation of marketing activities. The results show that the use of Integrated Marketing Communication (IMC) elements such as social media, advertising, public relations, sales promotions, and direct communication can increase brand attention and recognition. Instagram profile visits increased by 78.9% during the digital campaign, while Google Ads generated 8,180 impressions, 441 clicks, with a CTR of 5.39%. These findings indicate that IMC contributes to increasing brand recognition and brand recall sustainably in the hospitality sector. Supporting factors for success include visual identity consistency, internal team coordination, utilization of social media insights, and product excellence as a one-stop destination.